A Curve-fit Traction Coefficient Relation of Mixed EHL Line Contact with Hydraulic Fluid and Steel Surfaces. Issue 2 (4th March 2023) - Manne, Venkata Harish Babu; Vacca, Andrea; Singh, Kushagra
Abstract: Accurate modeling of hydraulic gear machine meshing torque loss, considering possible asperity contact, is required for better prediction of its hydromechanical efficiency. A model for predicting the mixed thermal EHL line contact traction coefficient is implemented in this study, considering experimental density and viscosity properties. Simulation results of traction coefficient are validated with experiments at two operating conditions. The defining components of the traction coefficient, the asperity load ratio and the hydrodynamic component are obtained at wide range of inputs. Finally, explicit curve-fit formulations of the asperity load ratio and the hydrodynamic component of traction coefficient are created in terms of input non-dimensional variables, which can be used for modeling the torque loss in a simple yet accurate way.